Enhancement of some sex hormones concentrations by consumption of leaves extract of Viscum album (mistletoe) in rats - Ofem, Ofem Effiong; Antai, Atim Bassey; Essien, Nsima Monday; Oka, Victor Otu (Asian Journal of Medical Sciences, 2014)
Objective: This present study was conducted with the aim to investigate the effect of consumption of leaves extract of mistletoe on the concentration of some serum sex hormones (follicle stimulating hormone (FSH), luteinizing hormone (LH), testosterone and prolactin) in rats. Methods: Twenty-four (24) female albino Wistar rats (210-250 g final body weight) were randomly assigned into 4 groups of 6 rats each. Group 1 (control) took normal rat chow + drinking water. Group 2, extract treated-1 (ET-1), group 3, extract treated-2 (ET-2) and group 4, extract treated-3 (ET-3) in addition received 150 mg/kg, 300 mg/kg and 450 mg/kg respectively of V. album extract p.o once daily. The feeding regimens lasted for 4 weeks. Results: The serum concentrations of FSH, LH, testosterone and prolactin in control group were 0.95±0.09 μIU/mL, 1.21±0.10 μIU/mL, 6.78±0.19 ng/mL and 1.86±0.09 ng/mL respectively. FSH levels was significantly (p<0.05) higher in ET-1 compared with control and ET-3. Serum concentrations of LH and testosterone were significantly (p<0.05) higher in ET-1 and ET-2 compared with control; LH and testosterone concentrations were in turn significantly (p<0.01) lower in ET-3 compared with ET-1 and ET-2. Prolactin decreased significantly (p<0.05) in ET-1 and ET-2 compared with control. Conclusion: Moderate and controlled doses of mistletoe extract increases serum levels of FSH, LH and testosterone but decreases prolactin concentrations, which could enhance reproductive functions in normal persons and those with loss-of reproductive function. Asian Journal of Medical Science, Volume-5(3) 2014: 87-90 http://dx.doi.org/10.3126/ajms.v5i3.9593